The Role of the Husband on Maternal Health during Pregnancy: A Scoping Review - Ratnaningrum, Asti; Suryaningsih, Endang Koni (Poltekita : Jurnal Ilmu Kesehatan, 2024)
The Maternal Mortality Rate (MMR) in Indonesia is 305/100,000 KH, which is still high, one of which is due to delays in the mother's decision-making. Socio-cultural influences prevent women from making decisions independently during pregnancy, childbirth, and postpartum because the husband is still the center of service decision-making. This study aims to determine the existing literature review regarding the husband's role in maternal health during pregnancy. The method used is Four database searches were carried out using the PRISMA ScR agenda methodology on Science Direct, EBSCOhost, and Exploration Hare. Data were searched based on research objectives, year of publication, research design, characteristics of respondents, and research context—critical Appraisal using JBI Critical Appraisal Tools. The results of the study show that seven articles were selected for review. Each piece in this review covers various subjects related to estimation, mediation, methodology, and research results and shows that the role of husbands in developing countries during pregnancy and the postpartum period is most influenced by cultural norms. This finding shows how culture affects the position of men as having primary responsibility for the family's financial well-being. At the same time, women are expected to take on household responsibilities such as cooking, caring for children, cleaning, and washing.